The Effect of Various Concentrations of Gossypol on The Rumen Protozoal Degradation of Grass Hay in Culture - Ismartoyo (Ismartoyo) (Faculty of Animal Science, Universitas Gadjah Mada, 2003)
Artikel dalam bentuk PDF